A right to pollute versus a duty to mitigate: on the basis of emissions trading and carbon markets. (9th August 2022) - Espinosa-Flor, Sarah Isabel
ABSTRACT: Emissions trading, also known as cap-and-trade systems, has not yet fulfilled its function of mitigating overall global greenhouse gas (GHG) emissions. The reasons for this failure are manifold and have been broadly discussed at political and empirical levels in the last decades. However, much can still be said from a philosophical perspective. Such an analysis is not limited to the evaluation of cap-and-trade systems' lack of efficiency and the consequences arising from it but goes deeper into the moral questions underlying cap-and-trade systems. This is how this paper attempts to contribute to and expand the debate on emissions trading at different levels. By examining a popular analogy between traditional and climate commons, I challenge some of the economic and normative assumptions at the core of cap-and-trade systems. I argue that these assumptions lead to misguided conclusions in responding to the causes of climate change. This will partly explain why, although emissions trading is intended to fulfil a duty to mitigate greenhouse gases, we should not pin all our hopes on it just yet. Key policy insights The problems associated with free access to the traditional and climate commons can be conceived of in an analogous way, but the solutions to address them cannot. These include market-based policies focusing on the distribution of property rights over the atmosphere's capacity to absorb GHGs. Like other common resources, the atmosphere's capacity to absorb GHGs is limited and subject to deterioration due to free access and competing consumption. Unlike other common resources, there is no ability to restrict, control or sanction non-cooperative behaviour that continues to pollute the atmosphere. This poses a major challenge to the effectiveness of cap-and-trade systems. Emissions trading systems can be attractive mechanisms for pursuing GHGs targets by minimizing the costs of pollution while limiting the impact of mitigation on the overall economy. Nevertheless, even efficient emissions trading systems fail to fully address the moral concerns that lie at the heart of our current climate crisis.